Establishing a Quality Management System for Production of Certified Customised Titanium Medical Implants through Additive Manufacturing - du Preez, W. B.; de Beer, D. J.; Booysen, G. J. (MRS advances, 2020)
Various cases of medical implants produced through additive manufacturing (AM) in Ti6Al4V have been reported in literature. Not all manufacturing processes used, were qualified. In striving to deliver certified AM medical implants and devices, an ISO 13485:2016 quality management system was implemented in the Centre for Rapid Prototyping and Manufacturing (CRPM) of the Central University of Technology, Free State (CUT) in Bloemfontein, South Africa. This certification is valid for design, development and production of patient-specific custom-made titanium implants, preoperative models, jigs and cutting-guides in nylon through AM, and contract-production of these products. For maintaining this quality management system, the generation of data to validate the individual processes in the AM process-chain is crucial to prove the DMLS product-quality of CRPM’s products. During the past five years, directed research data was produced and published to prove that medical implants produced through DMLS can fully comply with the accepted international standards for material, physical, chemical and mechanical properties of such parts. The paper discusses the quality management system’s establishment; materials research projects executed to generate validation data are mentioned; and examples of customised titanium implants for restoring the quality of life of patients are shown.